Assessment of redistribution policies in Singapore - Ang, Xin Rui (Nanyang Technological University, 2021)
Singapore is recognised as one of the richest countries in the world. However, income inequality has continued to exacerbate in recent years, with the country ranking 107 out of 158 countries based on the Commitment to Reducing Inequality Index (Inequality Index, 2020). A study conducted by the National University of Singapore’s Social Service Research Centre found that an estimated 12% of Singapore households are not earning enough to meet their basic needs, further highlighting the trend of increasing income inequality (Ng et al., 2018).